Lonicera japonica polysaccharides attenuate ovalbumin-induced allergic rhinitis by regulation of Th17 cells in BALB/c mice - Xinyu Bai; Yeewen Chai; Wanlan Shi; Yingying Li; Tao Zhang; Ping Liu (Elsevier, 2020)
Lonicera japonica Thunb. has been widely used as food ingredients and healthy drinks in the Asian countries, which was reported to possess some good activities. However, it remains unknown in the immunomodulation of Lonicera japonica polysaccharides (LJP) on allergic rhinitis (AR). This study aimed to investigate the impact of LJP on ovalbumin-induced AR in BALB/c mice model. LJP significantly inhibited AR symptoms and eosinophil number in nasal mucosa. Besides, the increased serum levels of IgE, TNF-α, IL-1β and IL-17 were markedly decreased when AR mice were treated with LJP. The mRNA expression levels of IL-4, IL-5, IL-6, IL-17, IL-23, ROR-γt and STAT3 in OVA group were increased, and SOCS3 was reduced, while LJP inhibited the changes. The present study indicated that LJP suppressed the inflammatory response in AR sensitized by ovalbumin, showing that LJP has the potential to treat AR through the regulation of Th17 cells.